An analysis of the continuing professional development needs of radiographers and radiation therapists in Singapore. Issue 3 (August 2021) - Mohamed Afif, A.; Goh, M.Z.H.; Lin, Y.J.; Ho, G.D.; Anwar, T.; Chong, C.M.; Sim, J.
Abstract: Introduction: Continuing Professional development (CPD) is deemed essential for the Radiographers (DR) and Radiation Therapists (RT) after Singapore commenced state registration. Diagnostic imaging and radiotherapy treatment services are constantly revolutionizing and those working in this field requires sufficient knowledge of the uptrends for training and development. The purpose of this survey is to identify the current training needs of the registered DR and RT in Singapore, and to understand their views about CPD activities. Methods: An online questionnaire was disseminated by the Singapore Society of Radiographers (SSR) to all registered DR and RT in Singapore, and all practicing in restructured and private hospitals were included. Data collection took place from January 2018 to April 2018. Results: 102 responses were analysed, where 89 were DR and 13 were RT. CPD was provided in 72.5% (n = 74) of the participants' institutions, and 69.6% (n = 71) of participants were aware of CPD. Interestingly, participants were significantly more likely to be unaware of CPD when working in an institution which do not offer CPD. Training programme objective was the most important factor for selecting a programme. 93.1% (n = 95) preferred SSR to support them for CPD. There were a few constraints to CPD engagements identified such as financial factors, lack of time, and institution availability. Conclusion: There was significant intrinsic motivation in a quality CPD activity. CPD activities should be current, accessible and relevant for the healthcare professionals to increase participation, which directly contributes to high standards of clinical care. Implications for practice: Local healthcare institutions should be aware and address needs, gaps and aspirations of the local DR and RT community to ensure adequate preparation has been made upon initiation of mandatory CPD.